The Correlation Between Knowledge and Self-Management Compliance in Type 2 Diabetes Mellitus Patients at The Regional Hospital Of Pringsewu - Nanda Okta Anggraini; Hana Zumaedza Ulfa; Hardono Hardono; Sulistia Nur (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: To determine “The Correlation Between Knowledge and Self-Management Compliance in Type 2 Diabetes Mellitus Patients At The Regional Hospital Of Pringsewu”. Method: This study was a quantitative study with a cross-sectional design and purposive sampling technique. The population was all type 2 diabetes mellitus patients at the Internal Medicine Polyclinic of Pringsewu Regional Hospital, with a sample of 79 respondents who met the inclusion and exclusion criteria. The research instrument used the Diabetes Knowledge Questionnaire 24 (DKQ-24) for knowledge and the Diabetes Self-Management Questionnaire (DSMQ) for self-management compliance. Data analysis was performed using the Gamma test. Result: The results obtained based on the gamma statistical test showed that there was a Correlation Between Knowledge and Self-Management Compliance in Type 2 Diabetes Mellitus Patients At The Regional Hospital Of Pringsewu with a p-value of 0.001. Conclusion: It was concluded that knowledge can influence self-management compliance in type 2 diabetes mellitus patients.